Trends in pediatric cochlear implants: The dual impact of COVID-19 and Lebanon’s crisis - Joy M. El Maalouf; Maged T. Ghoche; Gabriel Dunya (PLoS ONE, 2025)
Background Hearing loss is a major public health issue globally, especially in low- and middle-income countries (LMICs), where access to cochlear implants (CIs) is restricted by cost and limited healthcare infrastructure. In Lebanon, the 2020 economic crisis and the COVID-19 pandemic further reduced access to essential services, including pediatric CIs. Aim This study assesses the impact of the 2020 Lebanese economic crisis on the number and funding sources of pediatric CI surgeries. Methods A retrospective review was conducted on 228 pediatric patients who underwent 235 CI surgeries between 2017 and 2023. The number of surgeries and funding sources were compared before and after the 2020 crisis. Funding categories included government, private insurance, donations, or a combination. Data were analyzed using R software. Results There was no significant difference in the number of surgeries before (113) and after (122) the crisis (p = 0.56). However, a marked shift in funding occurred. Government-funded procedures dropped from 45.87% to 12.61% (p < 0.001), while private and donation-based funding rose from 32.11% to 66.39% (p < 0.001). The mean age at surgery declined from 5.86 to 3.57 years post-crisis (p < 0.05), indicating greater awareness of early intervention benefits. Conclusion Despite economic hardship, the demand for pediatric CIs persisted, with families turning to private and charitable sources. Enhanced government support and the classification of CIs as essential health services are vital. Early diagnosis and intervention should be prioritized to improve outcomes in children with hearing loss.